2021
DOI: 10.1021/acs.jmedchem.0c02173
|View full text |Cite
|
Sign up to set email alerts
|

Use of Intramolecular 1,5-Sulfur–Oxygen and 1,5-Sulfur–Halogen Interactions in the Design of N-Methyl-5-aryl-N-(2,2,6,6-tetramethylpiperidin-4-yl)-1,3,4-thiadiazol-2-amine SMN2 Splicing Modulators

Abstract: Spinal muscular atrophy (SMA) is a debilitating neuromuscular disease caused by low levels of functional survival motor neuron protein (SMN) resulting from a deletion or loss of function mutation of the survival motor neuron 1 (SMN1) gene. Branaplam (1) elevates levels of full-length SMN protein in vivo by modulating the splicing of the related gene SMN2 to enhance the exon-7 inclusion and increase levels of the SMN. The intramolecular hydrogen bond present in the 2-hydroxyphenyl pyridazine core of 1 enforces … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 40 publications
(76 reference statements)
0
9
0
Order By: Relevance
“…The SMN2 compounds 1 and 2 both assume a planar structure in the core region as necessitated by the bicyclic core present in 1 and by the intramolecular hydrogen bonding (HB) interaction in 2 . Similar conformational preference is presumably operating in the fluorinated benzamide core of 3 where an intramolecular HB (F---HN) locks the aryl amide in a plane . Whether the ortho -F-amide group in 3 was near optimal for the targeted HTT activity was unclear at the onset.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SMN2 compounds 1 and 2 both assume a planar structure in the core region as necessitated by the bicyclic core present in 1 and by the intramolecular hydrogen bonding (HB) interaction in 2 . Similar conformational preference is presumably operating in the fluorinated benzamide core of 3 where an intramolecular HB (F---HN) locks the aryl amide in a plane . Whether the ortho -F-amide group in 3 was near optimal for the targeted HTT activity was unclear at the onset.…”
Section: Resultsmentioning
confidence: 99%
“…5-Chloro-N-(8-fluoro-2-methylimidazo[1,2-a]pyridin-6-yl)pyrazine-2-carboxamide (102A, 70 mg, 0.23 mmol), (S)-N-methylpyrrolidin-3-amine (23 mg, 0.23 mmol), cesium carbonate (325 mg, 1 mmol), and DMF (2 mL) were combined in a sealed tube and heated to 100 °C for 16 h. The reaction mixture was cooled to rt, cesium salts (22). 5-Chloro-N-(8-fluoro-2-methyl-imidazo[1,2-a]pyridin-6-yl)pyrazine-2-carboxamide (102A, 127 mg, 0.415 mmol), cesium carbonate (271 mg, 0.831 mmol), (R)-3-(boc-amino)pyrrolidine (77 mg, 0.415 mmol), and 1,4-dioxane (15 mL) were combined in a sealed tube and heated to 100 °C for 4 h. The reaction mixture was cooled to rt.…”
Section: (S)-n-(8-fluoro-2-methylimidazo[12-a]pyridin-6-yl)-5-(3-(met...mentioning
confidence: 99%
“…As a result of this increased flexibility, the majority of compounds in the series show good anti‐PC activity. Very interestingly, for the first time we found that electronic effect of the substituent plays a major role on the activity compounds; it means that the electronic effect of the substituents influences the strength of the non‐covalent interactions, which influences the free rotation of the benzene ring with respect to the pharmacophore, resulting in change of activity (Axford et al, 2021). Furthermore, the synthesized compounds lack any sort of amide functional group, which is a key functional group for both first and second‐generation approved drugs.…”
Section: Discussionmentioning
confidence: 98%
“…More recently, the central benzene ring in the symmetrically disposed diprivomicin 120a has been found to be recalcitrant to replacement with the more conventional isosteres cyclohexane ( 120b , 120c ), acetylene ( 120d ), ethylene ( 120e ), and thiophene ( 120f ), with only pyridine ( 120g ) being effective among the motifs examined, although the survey conducted was restricted in scope . Indeed, there are a number of drug pharmacophores and binding sites that demand planarity, reflecting a need for the design of new phenyl ring mimics that can capture key aspects of drug–target interactions or scaffolding functions while abrogating some of the developability liabilities associated with a benzenoid ring. …”
Section: Conclusion and Perspectivementioning
confidence: 99%